Addressing Filicide in Ghana: Linking Cultural Understanding With the Law Against Filicide. Does the Law Work? - Abdullah, Alhassan; Frederico, Margarita; Mensah, Felix; Bentum, Hajara; Wang, Yihang; Asare, Jennifer Litela (Frontiers in Psychology, 2022)
Introduction Consistent with international promulgation on the criminalization of filicide, Ghana’s Children’s Act 1998 (560) and the Criminal Justice Act criminalizes any form of torture against children. Yet, perpetrators of filicide in Ghana may go unpunished due to the beliefs in cultural norms that justify filicide acts. The cultural narratives of filicide can impede on the application and effectiveness of the laws of filicide. Method The study employed a vignette approach to explore the views of 19 adults, who were parents between 69 years of age and 30 years of age, in rural and urban Ghana on the laws of filicide in Ghana and filicide intervention measures. The interviewees were provided with narratives on two different vignettes (developed based on real life cases), followed by semi-structured questions to probe the narratives. The interviews were analyzed following Fraser’s narrative thematic analysis procedure. Results The study identifies the association between cultural beliefs and the communities’ understanding of the concept of filicide. Though community members are aware of the criminalization of filicide acts, the majority of them were not informed about the laws against filicide in Ghana. Addressing filicide cases within the community was the most preferred option for the participants, as they believe that some children, termed “spirit children” (SC), deserve to be killed. Resorting to spiritual intervention from concoction men emerged as the normative pathway to obtain community approval for filicide. Police interventions were considered necessary in non-spiritual related filicides. Community members were only prepared to cooperate with the law in filicide cases if the filicide act has no connection with spirituality. Conclusion The study adds to understanding of the concept of filicide outside western societies. The importance of intensive community campaigns against filicide acts, and norms that support filicide acts, has relevance for all counties.